Alternative catalytic materials : carbides, nitrides, phosphides and amorphous boron alloys - Hargreaves, J. S. J.; McFarlane, Andrew R.; Laassiri, Said (Royal Society of Chemistry, 2018)
An important reference for researchers and industrialists working in heterogeneous catalysis and materials chemistry.
Includes index.
Title from title details screen.
Keywords: Catalysts.; Catalysis.; elektronické knihy; electronic books